Improving the stability of discretization zeros with the Taylor method using a generalization of the fractional-order hold - Zeng, Cheng; Liang, Shang; Zhang, Yuzhe; Zhong, Jiaqi; Su, Yingying (Zielona Góra: Uniwersytet Zielonogórski)
Remarkable improvements in the stability properties of discrete system zeros may be achieved by using a new design of the fractional-order hold (FROH) circuit. This paper first analyzes asymptotic behaviors of the limiting zeros, as the sampling period T tends to zero, of the sampled-data models on the basis of the normal form representation for continuous-time systems with a new hold proposed.
Keywords: stability; discretization zeros; Taylor method; signal reconstruction; sampled-data model